2017
DOI: 10.1016/j.socec.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the relationship between skill and overconfidence

Abstract: The Dunning-Kruger effect states that the low skilled are overconfident while the high skilled are more accurate in assessing their skill. In apparent support of this effect, many studies have shown that low performers overestimate their performance while high performers are more accurate. This empirical pattern, however, might be a statistical artifact caused by measurement error. We are the first paper to consistently estimate the Dunning-Kruger effect using an instrumental variable approach. In the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 19 publications
4
41
0
Order By: Relevance
“…Kruger and Dunning ( 1999 ) concluded that low-performing students significantly overestimate their performance, while high-performing students are more accurate in their forecasts. Feld et al ( 2017 ) pointed out that this effect could at least partially be explained by measurement errors. They showed that after correction for measurement errors (using instrumental variables) the Dunning-Kruger effect is still observed, but significantly weaker than before the correction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kruger and Dunning ( 1999 ) concluded that low-performing students significantly overestimate their performance, while high-performing students are more accurate in their forecasts. Feld et al ( 2017 ) pointed out that this effect could at least partially be explained by measurement errors. They showed that after correction for measurement errors (using instrumental variables) the Dunning-Kruger effect is still observed, but significantly weaker than before the correction.…”
Section: Resultsmentioning
confidence: 99%
“…Expectations move closer to the realized grade as students receive new information on their actual performance closer to the exam. Many other papers reject the hypothesis of rational expectations and confirm student grade overconfidence; see Kruger and Dunning ( 1999 ), Svanum and Bigatti ( 2006 ), Andrews et al ( 2007 ), Burns ( 2007 ), Jensen and Moore ( 2008 ), Khachikian et al ( 2011 ), Hossain and Tsigaris ( 2013 ), Feld et al ( 2017 ), Foster et al ( 2017 ), Serra and DeMarree ( 2016 ), and Sturges et al ( 2016 ).…”
Section: Introductionmentioning
confidence: 97%
“…Since the seminal paper establishing the DKE, there has been debate over whether the effect derives from metacognitive differences between skilled and unskilled people (Kruger & Dunning, 1999), from general biases of self-estimation (Burson et al, 2006;Krueger & Mueller, 2002), or from statistical artefacts (Feld et al, 2017;Krajc & Ortmann, 2008;Krueger & Mueller, 2002). Despite vigorous defences of the metacognitive account (Dunning, 2011;Ehrlinger et al, 2008;Kruger & Dunning, 2002;Schlösser, Dunning, Johnson, & Kruger, 2013), and its enthusiastic dissemination through the wider culture, unambiguous evidence has not been provided, and the debate has persisted.…”
Section: Discussionmentioning
confidence: 99%
“…Competing accounts of the DKE focus on other mechanisms that might induce this negative correlation. One mechanism often invoked is regression to the mean (Ackerman, Beier, & Bowen, 2002;Burson, Larrick, & Klayman, 2006;Feld, Sauermann, & de Grip, 2017;Krueger & Mueller, 2002;Nuhfer, Cogan, Fleisher, Gaze, & Wirth, 2016;Nuhfer, Fleisher, Cogan, Wirth, & Gaze, 2017). A common method for studying the DKE involves ranking people by task performance and examining the relationship with estimation error, as indexed by the subtraction of actual from estimated performance; a negative correlation is virtually guaranteed in this scenario; just as, for any two imperfectly correlated random variables, x correlates negatively with y-x.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation